Changes in the Hematology Parameters of Freshwater Fish Channa striatus Exposed to the Pesticide of Propargite: Changes in the Hematology Parameters of Freshwater Fish Channa striatus Exposed to the Pesticide of Propargite - Sivasuriyan, S. (International Journal of Pharmaceutical & Biological Archive, 2019)
In the present study was sublethal concentrations of propargite pesticide administered to freshwater fish C. striatus for 96 hours propargite exposure is 0.34 parts per million (ppm) based on the period of (0.034ppm), (1.02ppm), 15 and 30 days about significantly (P > 0.05) in hematological parameters alterations was recorded. The hematological analysis showed significant (P > 0.05) reduction in red blood cell count, hemoglobin value, packed cell volume, mean corpuscular hemoglobin (MCH), MCH concentration, and mean corpuscular volume. The parameters such as total white blood cells increased when induced toxic content. The present study indicated marked changes in the blood of C. striatus after exposure to propargite pesticide.